2012
DOI: 10.1371/journal.pmed.1001158
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Resource Utilization by Children with Neurological Impairment in the United States Inpatient Health Care System: A Repeat Cross-Sectional Study

Abstract: Jay Berry and colleagues report findings from an analysis of hospitalization data in the US, examining the proportion of inpatient resources attributable to care for children with neurological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
171
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(185 citation statements)
references
References 36 publications
9
171
1
4
Order By: Relevance
“…Neurologic impairment is defined as "functional and/or intellectual impairments that result from a variety of neurologic diseases" (eg, anoxic brain injury, lissencephaly). 8 Patients with technology dependence "depend on medical technology to live or remain in their current state of health" (eg, tracheostomy, enteral feeding tube, cerebral spinal fluid shunt). 9,10 The majority of these children (55%) receive outpatient care at CCHMC's Complex Care Center, a medical home that provides primary care to 620 children with severe, chronic disease who receive care from ≥3 subspecialists.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurologic impairment is defined as "functional and/or intellectual impairments that result from a variety of neurologic diseases" (eg, anoxic brain injury, lissencephaly). 8 Patients with technology dependence "depend on medical technology to live or remain in their current state of health" (eg, tracheostomy, enteral feeding tube, cerebral spinal fluid shunt). 9,10 The majority of these children (55%) receive outpatient care at CCHMC's Complex Care Center, a medical home that provides primary care to 620 children with severe, chronic disease who receive care from ≥3 subspecialists.…”
Section: Settingmentioning
confidence: 99%
“…However, the discharge process for medically complex patients remained inefficient; only 50% of patients on the HM service with neurologic impairment 8 and/or technology dependence 9,10 were discharged within 2 hours of meeting medical discharge goals. Preliminary work revealed that the medical team often overlooked the particular discharge needs of these medically complex patients and their families until after a child was medically ready for discharge.…”
mentioning
confidence: 99%
“…We used ICD-9-CM diagnostic and procedure codes described in previous studies to identify new medical technology inserted in the terminal admission. [14][15][16]26,27 Medical technology refers to any device that helps maintain health status and physiologic function (eg, gastrostomy or tracheostomy tube). 14 …”
Section: Outcome Measuresmentioning
confidence: 99%
“…Children are increasingly admitted to the hospital for invasive procedures and initiation of medical technologies to maintain health. [14][15][16][17] Consequently, children with LT-CCCs now account for a substantial proportion of pediatric hospital resource use. [17][18][19][20] Although advancements in hospital care have improved life expectancy for some children with LT-CCCs, many ultimately acquire multiple comorbid conditions as they age.…”
mentioning
confidence: 99%
“…Factors to consider when evaluating the economic impact of these disorders include the costs of diagnostic tests, medical services, referrals to specialists, medications, social services for children, and missed work or underemployment for caregivers. 9 Analyses based on the Kids' Inpatient Databases found that seizures accounted for 16.9% of hospital admissions in 2006, 10 with an estimated annual cost per patient of $4,553.…”
Section: Model Structure and Inputsmentioning
confidence: 99%